E-133 Adherence to endovascular treatment guidelines in acute ischemic stroke: insights from an international multidisciplinary survey. (22nd July 2019) - Ospel, J; Kashani, N; Wilson, A; Kunz, W; Sylaia, P; Baxter, B; Campbell, B; Fischer, U; Rabinstein, A; Yoshimura, S; Heo, J; Kim, B; et al.
Abstract : Background: Several randomized controlled trials have provided level IA evidence for the efficiency of endovascular therapy in acute ischemic stroke. We assessed the adherence to current endovascular treatment guidelines in acute ischemic stroke according to geographical region, hospital setting, medical specialty and physicians' characteristics. Methods: An international cross-sectional survey of stroke physicians and interventionalists was conducted to understand their current practice and therapy decision-making in acute stroke. Participants were randomly assigned 10 cases out of a pool of 22 scenarios and asked how they would treat the patient. Adherence to the 2018 Guidelines for the Early Management of Patients with Acute Ischemic Stroke From the American Stroke Association was analyzed, and subgroup analyses were performed for different geographical regions, hospital settings, medical subspecialty, physician experience and age. Results: 607 physicians (53.6% neurologists, 28.7% interventionalists, 13.3% neurosurgeons, 4.7% other) from 38 countries participated in this survey. Overall guideline adherence in cases based on level of evidence 1A and 2B was 86.1% and 66.6%. For level 1A case scenarios, adherence differed significantly across different specialties (ranging from 90.4% to 56.5%, p<0.001) and different geographic regions (ranging from 89.9% to 72.0%, p<0.001). Physicians with a higher adherence to treatment guidelines performed significantly more EVT cases per year than those with a lower adherence (median 30, IQR 35 vs. 15, IQR 25, p<0.001). In level 2B scenarios, the overall decision rate in favor of EVT was lower (66.6%) and the differences in decision rates between different specialties (73.7% - 40%, p<0.001) and regions (73.9% - 47.1%, p<0.001) were more pronounced. Again, physicians opting for EVT performed significantly more EVTs per year (median 30, IQR 30 vs. 20, IQR 30, p<0.001). Conclusion: The high overall adherence to current endovascular stroke treatment guidelines suggests strong consensus within the neurointerventional community. Physician caseload played an important role in our sample. Disclosures: J. Ospel: None. N. Kashani: None. A. Wilson: None. W. Kunz: None. P. Sylaia: None. B. Baxter: None. B. Campbell: None. U. Fischer: None. A. Rabinstein: None. S. Yoshimura: None. J. Heo: None. B. Kim: None. M. Cherian: None. F. Turjman: None. M. Foss: None. B. Menon: None. G. Saposnik: None. M. Hill: None. M. Goyal: None. M. Almekhlafi: 1; C; unrestricted research grant by Stryker to the University of Calgary.